Spiders Behaving Badly in the Middle English Physiologus, the Bestiaire Attributed to Pierre de Beauvais and Odo of Cheriton's Fables. - Cavell, Megan (Neophilologus, 2020)
Two remarkably similar depictions of spiders survive in Middle English and French sources from the middle of the thirteenth century. Both of these vernacular versions of the Physiologus deviate so wildly from their sources when it comes to describing these creatures that their editors have declared these passages to be entirely original. And yet, the spiders who survive in the Middle English Physiologus and the long version of the Bestiaire attributed to Pierre de Beauvais perform such similar work that their originality may be called into question. The Physiologus' and Bestiaire's descriptions of spiders' violent hunting methods were likely informed by the burgeoning of natural history writing that accompanied the recovery of Aristotle's History of Animals, but for these texts' allegorical interpretations I argue that we should look to Odo of Cheriton's Latin fables from earlier in the thirteenth century. There is an explicit link between Odo's fables and the Middle English Physiologus and implicit connections with the French Bestiaire. Together, these analogues demonstrate a small but coherent tradition of emphasizing the diabolical violence of spiders in the multilingual environment of thirteenth-century England and France.